532 Shedding a light on grey literature searches for occupational health topics: a belgian case study on chemicals exposure. (24th April 2018) - Temmerman, AM; Ronsmans, S; Pauwels, S; Rusu, D; De Schryver, A; Godderis, L; Braeckman, L
Abstract : Introduction: For occupational health topics with hardly any published white literature available, grey literature can be a generous information source. This abstract describes the search and use of grey literature in preparation of the PROBE (Hazardous chemical P roducts R egister for O ccupational use in Be lgium) study, aiming to map both occupational exposure to chemicals in Belgian workers and the need for knowledge about such exposure. Methods: A cascade of methods was applied. First, relevant associations, organisations, agencies and bodies were identified through interviews with field experts and general internet search engines. Then, specific domains within Google Advanced Search were applied to geographically limit the results to Europe and Belgium. As quality filters, the domain limits org, edu and gov were applied. A second approach consisted in specific grey literature gateways. Finally, references in retrieved documents were explored for additional information sources. Results: This multifaceted approach generated a comprehensive overview of evidence based data. The compiled information can be categorised as databases with exposure data and chemical risk assessments, data from similar research in other countries, methodological insights in chemicals selection and exposure surveillance techniques, interim reports of ongoing research, reports, white papers, and legislation. The pathway of grey literature databases was abandoned, as its literature was outdated. The retrieved information provided us with the necessary acumen in the selection of relevant chemicals and appropriate assessment strategies to strengthen the proposed study protocol. Discussion: A grey literature search is a challenging and lengthy process as the information is dispersed, hard to access and fragmented. The standard review methods for white literature do not apply to grey literature searches. The complex architecture of grey literature requires an innovative, creative and iterative approach. Nevertheless we succeeded in tapping valuable information from this source. Further initiative is needed to improve grey information availability and retrieval.